Qualitative Design in Political Communication Research, Surveys and Public Opinion - BOESTAM, Ambia B.; CANGARA, Hafied; IRWANTI, Marlinda; DERIVANTI, Azizah Des (PT Keberlanjutan Strategis Indonesia, 2023)
Differences in perspective, scientific background, and understanding of a researcher often become a paradigm that will affect the methods used in compiling design research, which leads to how to formulate problems, determine data collection techniques, analyze data, and so on. This article discusses how the grounded theory method is applied in political communication research, surveys, and public opinion with a qualitative research approach. Qualitative research using the grounded theory method starts from the data to reach a theory. It does not start from a theory or test a theory, so in grounded theory research, it is necessary to have various procedures or steps that are systematic and well-planned. Researchers observe, collect, and organize data and form theories from the data simultaneously. One of the essential techniques in grounded theory research is the constant comparison process in which each piece of data is compared with all other data one by one. The grounded theory method is applied in political communication research, surveys, and public opinion with a qualitative research approach, starting from the data to reach a theory and not starting from a theory or testing a theory. One of the essential techniques in grounded theory research is the constant comparison process. fixed) where each data is compared with all other data one by one.